2018
DOI: 10.1098/rsos.180738
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and switchable dielectric behaviours in an organic–inorganic hybrid compound: (3-nitroanilinium) 2 (18-crown-6) 2 (H 2 PO 4 ) 2 (H 3 PO 4 ) 3 (H 2 O)

Abstract: An organic–inorganic hybrid compound with an extensive three-dimensional (3D) crystal structure, (3-nitroanilinium)2(18-crown-6)2(H2PO4)2(H3PO4)3(H2O) (1), was synthesized under slow evaporation conditions. Differential scanning calorimetry measurements indicated that 1 underwent a reversible phase transition at ca 231 K with a hysteresis width of 10 K. Variable-temperature X-ray single-crystal diffraction revealed that the phase transition of 1 can be ascribed to coupling of pendulum-like motions of its nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…[45] According to the classification of phase transitions proposed by Buerger, [46] the observed structuralc hanges shouldc orrespond to as econd-order phase transition called displacive. This kind of transition has been mostly reported in hybrid compounds [47] and metallic salts, [48] and therefore its presence may be of great relevance to fully understand the behavior of crystalline molecular machines. It has been reported that these transformationsr equires malle nergy and are associatedw ith changes in the atomic positions of the molecular components due to moleculart ranslationso rr otations.…”
Section: Dynamiccharacterization By Variable-temperature (Vt) X-ray D...mentioning
confidence: 89%
“…[45] According to the classification of phase transitions proposed by Buerger, [46] the observed structuralc hanges shouldc orrespond to as econd-order phase transition called displacive. This kind of transition has been mostly reported in hybrid compounds [47] and metallic salts, [48] and therefore its presence may be of great relevance to fully understand the behavior of crystalline molecular machines. It has been reported that these transformationsr equires malle nergy and are associatedw ith changes in the atomic positions of the molecular components due to moleculart ranslationso rr otations.…”
Section: Dynamiccharacterization By Variable-temperature (Vt) X-ray D...mentioning
confidence: 89%
“…For reversible phase transition solid materials, the phase transition is generally accompanied by an anomaly of dielectric properties. 56,59,60 The dielectric constant vs. temperature curves of compounds 1 and 2 are presented in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the special physical properties of high-permittivity materials can be used to realize new devices with special properties. 37,38 Fig. 4 The temperature-dependent powder X-ray diffraction patterns of compounds 1 (a) and 2 (b) (experimental).…”
Section: Dielectric Propertiesmentioning
confidence: 99%